Cold Florida - DePoy, Phillip (DePoy, Phillip. Foggy Moskowitz series., 2016)
"It's 1974 and Foggy Moskowitz, a Jewish car thief, is on the run from Brooklyn authorities. He ends up in Florida working for the first office of Child Protective Services. An unlikely child protection officer, but a tenacious one, he takes on an investigation to find a missing infant, taken from the hospital by her addict mother. But the case takes several unexpected turns as Foggy makes his way from seedy Fry's Bay to Seminole swampland and a vision quest. Along the way he encounters more than a few interesting characters, gains help from some of them, including John Horse, an Indian mystic, and works to foil a vast land-grab scam by an uber-rich felon." -- Dust jacket.